2015
DOI: 10.1111/bjh.13883
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system involvement by Waldenström macroglobulinaemia (Bing‐Neel syndrome): a multi‐institutional retrospective study

Abstract: Bing-Neel syndrome (BNS) is a rare complication seen in patients with Waldenström macroglobulinaemia (WM), in which lymphoplasmacytic lymphoma (LPL) cells colonize the central nervous system (CNS). In this retrospective multi-centre study, we present the clinicopathological features, imaging findings, therapy, response and outcomes of 34 patients with BNS. The median time from WM diagnosis to BNS diagnosis was 3 years, 15% of patients were diagnosed with BNS at the time of WM diagnosis, and 22% of patients dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 33 publications
6
107
3
Order By: Relevance
“…Using a highly sensitive real time quantitative PCR (qPCR) technique, it has been demonstrated that MYD88 L265P can be detected in the CSF of BNS patients, and the mutation was also present in the CNS biopsy in one patient. 4,18,26 Moreover, disappearance of the MYD88 L265P by AS-PCR correlated with clinical and MRI response. Since the qPCR is a very sensitive technique, caution must be taken to avoid blood contamination of the CSF since MYD88 L265P can also be detected in peripheral blood.…”
Section: L265p Mutationmentioning
confidence: 77%
See 4 more Smart Citations
“…Using a highly sensitive real time quantitative PCR (qPCR) technique, it has been demonstrated that MYD88 L265P can be detected in the CSF of BNS patients, and the mutation was also present in the CNS biopsy in one patient. 4,18,26 Moreover, disappearance of the MYD88 L265P by AS-PCR correlated with clinical and MRI response. Since the qPCR is a very sensitive technique, caution must be taken to avoid blood contamination of the CSF since MYD88 L265P can also be detected in peripheral blood.…”
Section: L265p Mutationmentioning
confidence: 77%
“…3 In approximately 15% to 36% of patients, BNS was the presenting symptom with no previous history of WM. 3,4 These patients may have a better prognosis compared to patients with BNS and a previous history of WM. 4 The clinical suspicion of BNS in these patients with neurological symptoms was raised because of the presence of an IgM M-protein in the serum or the detection of a clonal Bcell population by multiparameter flow cytometry (MFC) in the cerebral spinal fluid (CSF).…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations